Performance of Particle Swarm Optimization for Sensor Networks: A Survey - Singh, Jagmeet; Kaur, Harpreet (International Journal of Computer Sciences and Engineering, 2015)
The Quality of Service provided by any network is affected by some specific factors. An efficient network achieves its goal by solving all the challenges and satisfies the factors. Many researchers develop several approaches, protocols, techniques, algorithms and methods to improve the performance of network. In this paper, we have conducted a survey to understand the problems of sensor network. The Swarm Optimization Algorithm is reviewed to solve these problems. We analyze that the particle swarm optimization is a capable algorithm to optimize each and every NP hard problems and develops an efficient network.